2016
DOI: 10.20450/mjcce.2016.1047
|View full text |Cite
|
Sign up to set email alerts
|

Minerals from Macedonia. XXX. Complementary use of vibrational spectroscopy and X-ray powder diffraction for spectra-structural study of some cyclo-, phyllo- and tectosilicate minerals. A review

Abstract: A review of the results of the complementary use of vibrational spectroscopy (infrared and Raman) and X-ray powder diffraction in the process of identification and spectra-structure correlation of some cyclo-, phyllo-and tectosilicate minerals originating from the Republic of Macedonia is presented. The following minerals are studied: schorl, Na(Fe 2+ ,Mg)3Al6(BO3)3Si6O18(OH)4; beryl, (Be,Mg)3Al2Si6O18; chrysotile, Mg3Si2O5(OH)4; antigorite, (Mg,Fe 2+ )3Si2O5(OH)4; talc, (Mg,Fe 2+ )3Si4O10(OH)2; clinochlore, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 100 publications
1
7
0
Order By: Relevance
“…From XRD analysis, it was confirmed that all clay samples had different compositions of mineral phases, including quartz, feldspar, phengite-3T, montmorillonite, vermiculite, muscovite, kaolinite, sanidine, phengite, and nacrite. This corroborated with the FTIR analysis (Figure 5) by comparing the observed wavenumbers with the available data in the literature [63,[69][70][71].…”
Section: Ftir Analysissupporting
confidence: 89%
“…From XRD analysis, it was confirmed that all clay samples had different compositions of mineral phases, including quartz, feldspar, phengite-3T, montmorillonite, vermiculite, muscovite, kaolinite, sanidine, phengite, and nacrite. This corroborated with the FTIR analysis (Figure 5) by comparing the observed wavenumbers with the available data in the literature [63,[69][70][71].…”
Section: Ftir Analysissupporting
confidence: 89%
“…The deconvolution of the spectral region of 1250-900 cm −1 (Figure 6) revealed seven bands belonging to quartz, albite, orthoclase and muscovite that can be divided into two parts. The first of these (1200-1050 cm −1 ) is related to Si-O and Si-O-Si bonds, and the second (1050-900 cm −1 ) arises mainly from the second type of bridging (i.e., Si-O-Al stretching) [28]. The bands at 1165 and 1090 cm −1 in albite and 1090 and 1060 cm −1 in quartz belong to the Si-O-Si stretching vibrations, whereas 1125 cm −1 can be attributed to Si-O stretching vibrations in orthoclase [29].…”
Section: Resultsmentioning
confidence: 99%
“…1125 cm −1 can be attributed to Si-O stretching vibrations in orthoclase [29]. The band at 1030 cm −1 belongs to Si-O bonds in quartz as well as to Si-O-Al in albite [28] and the Si(Al)-O stretching vibration in orthoclase [29]. Albite (NaAlSi3O8) and orthoclase (KAlSi3O8) are the extreme members of the plagioclase minerals, forming sodium and potassium feldspars, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Note that identical results can be obtained by averaging the imaginary part of the particle polarizability tensor, which corresponds to the high-dilution limit of the effective medium absorption in the Maxwell-Garnett approach (Eqs. 19 and 24 of Kendrick and Burnett, 2016; https://github.com/JohnKendrick/PDielec, last access: 15 July 2021). Ghaderi et al (2015) with the same xc-functional.…”
Section: Samples and Methodsmentioning
confidence: 99%
“…Independent constraints for the interpretation of the vibrational spectra of minerals can be gained from a theoretical approach. Previous modeling studies (e.g., Balan et al, 2001Balan et al, , 2002Kendrick and Burnett, 2016) have shown that it is possible to compute the powder IR spectra of minerals from firstprinciples quantum mechanical calculations with enough accuracy to provide useful constraints for the interpretation of experimental spectra. In the present study, we apply this welltested approach to the pristine antigorite m = 17 polysome whose structure has been previously investigated experimentally (Capitani and Mellini, 2004) and theoretically (Capitani et al, 2009).…”
Section: Introductionmentioning
confidence: 99%